Practical Management: A Standardized Aerobic Exercise Program for Adolescents With Concussion in the Absence of Graded Exercise Testing. Issue 3 (27th May 2023) - Chizuk, Haley M.; Haider, Mohammad N.; Edmonds, Jasmine Q.; Rawlings, Alex; Willer, Barry S.; Leddy, John J.
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Aerobic exercise is safe and beneficial for adolescent athletes recovering from sport-related concussion (SRC). The results of systematic graded exercise testing are used to create individualized, subsymptom heart rate threshold (HRt) aerobic exercise treatment programs for adolescents after SRC. Many clinicians, however, do not have access to graded exercise tests. This article presents a safe, systematic, evidence-based exercise program that clinicians can prescribe, progress, and modify to help manage acute pediatric SRC without the need for formal exercise testing. The exercise prescription accounts for sex and days since injury but not age because our analysis indicates age does not significantly affect the HRt on graded exercise testing. This article provides clinicians without access to graded exercise testing a viable option for prescribing exercise treatment to adolescents in the early phase after SRC.